The Influence Of Fiscal Policy On Agriculture Sector In Java Island - Siti Sabrina Salqaura; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Agro Ekonomi, 2018)
One of government interventions to encourage the improvement of agriculture sector output is through fiscal policy in the form of government spending. Total government expenditure in provincial aggregate is used as government spending. The availability of fiscal decentralization policy provides an opportunity for the provincial government to manage the government expenditure allocation. This research aims to discover the influence of fiscal policy in Java by using the government expenditure variable and to find the influence of foreign investment, domestic investment and agricultural labor absorption toward GRDP of agriculture subsectors. This research used regression analysis of cross section SUR fixed effect panel data. The results indicate the total expenditure having significant positive effect towards GRDP of agriculture subsectors are the subsectors of food crops, plantation, livestock and fishery. Forestry subsector cannot be analyzed further because the error is not normally distributed. The absorption of labor in agriculture sector has significant negative effect towards plantation and livestock subsectors. The foreign investment has significant positive effect towards livestock subsector and domestic investment has negative significant influence towards GRDP of food crops subsector. The provincial government needs to support agriculture subsectors by allocating expenditure that will increase GRDP of agriculture subsectors and increasing foreign direct investment and domestic investment to agriculture subsectors.